Sugars enhance parthenocarpic fruit formation in cucumber by promoting auxin and cytokinin signaling. - Wang, M.; Su, L.; Cong, Y.; Chen, J., Geng, Y.; Qian, C.; Qi, X
Parthenocarpy is an important agricultural trait that determines the yield of cucumber. The role of sugars in parthenocarpic fruit formation is unknown. Therefore, we investigated these factors by using one highly parthenocarpic line DDX and one weakly parthenocarpic line ZK. To identify the possible effect of photosynthesis on parthenocarpy, leaf of ZK and DDX were covered for limiting the synthesis of carbohydrates. Leaf covering inhibited parthenocarpic fruit initiation and growth. Sugars (sucrose, fructose and glucose)contents in CPPU-induced, pollinated fruit of ZK and non-pollinated fruit of DDX were higher than those in non-pollinated fruit of ZK. The exogenous application of sugars (especially fructose and sucrose)significantly induced the parthenocarpic fruit set and growth. Transcriptomes of fruits treated with and without exogenously applied sugars showed that genes involved in auxin signaling and cytokinin signaling were more strongly expressed in the treated fruits. Auxin responsive gene IAA14, and cytokinin responsive genes encoding histidine-containing phosphotransfer protein 4 and two-component response regulator 17 were upregulated in sugar-induced parthenocarpic fruits. These results show that parthenocarpic fruit formation is regulated by the interplay among sugars and the plant hormones auxin and cytokinin.
Keywords: AUXIN; CUCUMBER; CYTOKININ; PARTHENOCARPY; SUGAR